Total hip arthroplasty monobloc stem neck rupture in patient with massive heterotopic ossifications: a case report and literature review - Canton, Gianluca; Barbo, Giovanni; Roberto Fattori, Roberto; Nicholas Rasio, Nicholas; Murena, Luigi (Acta Biomedica Atenei Parmensis, 2023)
Background and aim of the work: Fractures of the femoral stem neck are a rare complication in hip prosthetic surgery, especially in non-modular components. The authors report a case associated with massive heterotopic ossifications, with the purpose to analyze risk factors and specific characteristics. Methods: A case of femoral monobloc stem neck rupture is described. A non-systematic literature review regarding risk factors for femoral stem neck fracture was conducted in the PubMed database. Results: We report the case of a 61-year-old male who underwent surgery to remove calcifications four years after THA. Four months later the patient reported acute pain in the left hip, arising after a combined movement of external rotation and axial load while standing on the left foot, in the absence of any prodromic symptom. On radiographs, a displaced fracture of the neck of the hip prosthesis was revealed, together with massive heterotopic ossifications. After THA revision the patient’s symptoms were resolved. Conclusions: Prosthetic femoral neck fractures are a rare complication. We suggest that this case represents a unique type of fatigue rupture, where neck length and the presence of massive heterotopic calcifications contributed to flexion forces, resulting in failure in the midpoint of the neck.